Representasi Gibran Rakabuming Dalam Dinamika Pemakzulan Wakil Presiden Pada Sampul Majalah Tempo Edisi 5 – 11 Mei 2025 - Yuwono, Andri Prasetyo (Kinesik, 2025)
This study analyzes the representation of Gibran Rakabuming Raka in the political context of the vice presidential impeachment discourse, as depicted on the cover of Tempo Magazine, edition May 5–11, 2025, titled "The Orchestra of Gibran’s Impeachment." The political momentum intensified after the Indonesian Military Retirees Forum officially submitted an impeachment request to the House of Representatives and the People’s Consultative Assembly. This study aims to identify the construction of meaning through visual and textual signs on the magazine cover, using the semiotic approach of Charles Sanders Peirce. A descriptive qualitative method is employed. The findings reveal that the media constructs Gibran’s image through a paradoxical visual narrative—serene in appearance, yet situated within a fragile and threatened political structure. The study concludes that mass media plays a strategic role in shaping public perceptions of political figures through non-neutral visual representation, especially in moments of leadership crisis.